2017
DOI: 10.1292/jvms.17-0017
|View full text |Cite
|
Sign up to set email alerts
|

Humeral fracture in a Japanese Black calf repaired by closed approach and two methods of external skeletal fixation

Abstract: A healthy 71-day-old female Japanese Black calf was evaluated for fracture of the left humerus. The left humeral fracture was treated by closed repair and unilateral external skeletal fixation (ESF) with an epoxy putty fixator. The calf was active, and eight days after surgery slipped and fell, resulting in breakage of the ESF. The calf underwent repair by transfixation pinning and casting (TPC), which is an alternative to the ESF method. The TPC was removed 37 days after the first surgery, and the calf could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The treatment cost is an important factor in the decision of surgical methods. Plate fixation is challenging in cattle because of its economic value (8,16).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment cost is an important factor in the decision of surgical methods. Plate fixation is challenging in cattle because of its economic value (8,16).…”
Section: Discussionmentioning
confidence: 99%
“…Reported surgical fracture treatments in cattle include external fixation techniques such as the use of circular external skeletal fixators10 11 or transfixation pins 12 13. Reported internal fixation techniques in cattle include intramedullary pinning,14 15 clamp rod internal fixators16 and use of DCPs 5.…”
Section: Discussionmentioning
confidence: 99%
“…Long bone fractures may occur in any part of calf bones due to trauma causes, such as incorrect interventions during difficult parturition, mother stepping on the calf, and falls and kicks. [1][2][3] Sarıerler and Kılıç 4 reported that 509 of the 1,918 patients that were seen in their clinics between 1999 and 2003 were cattle, 354 of which were calves. In addition, it was determined that 138 of 617 calves coming to our faculty clinic between January 2010 and May 2013 were referred due to long bone fracture, and these high numbers suggested that calf fractures should be studied.…”
Section: Introductionmentioning
confidence: 99%
“…3 In the treatment of fractures occurring in cattle calves, different methods are adopted, depending on the animal weight and the fracture type. [1][2][3][4][5] The most commonly used method is bandage-supported by American plaster cast (glass fibre) and polyvinyl chloride (PVC)-application. In addition, intramedullary pin, plate and screw or external fixator applications are recommended in some cases.…”
Section: Introductionmentioning
confidence: 99%